WE6.2 The true cost of pre-operative investigations. (9th August 2022) - Dholoo, Farzan; Shabana, Amanda; Burrows, Abigail; Horsnell, Jonathon
Abstract: Introduction: Pre-Operative Assessment (POA) is an integral part of surgery. It is essential for pre-operative investigations including bloods and COVID-19 swabbing. There was concern within the Breast-Unit that patients may be having unnecessary blood-tests as part of their POA. This was likely due to POA not having one unified resource to refer to. Guidance suggests POA uses the patient's American Association of Anaesthesiologist's (ASA) grade, type of surgery they are undergoing and additional conditions for determining pre-operative investigations. Methods: This QIP consisted of 2 cycles. During cycle-1 data was audited against national guidance to see which blood tests were performed unnecessarily. After developing a universal-guidance poster and teaching sessions, a second cycle was performed. Cycle-2 assessed whether there was a reduction in unnecessary blood tests being performed. Results: During cycle-1, 216 pre-operative blood tests were undertaken. Of these only 99 were required. Therefore 54% of the tests were unnecessary. This equates to £690.77 over 2-months and if extrapolated £4144.62 spent, unnecessarily per-year. This represents a significant cost to the trust and puts needless pressure onto the laboratory. During cycle-2, after our intervention, there were 57 fewer tests and 40 fewer, incorrect blood tests. Our intervention therefore resulted in a £183.46 saving, which over a year equates to £1110.76 saved. Conclusion: The potential benefits of improving POA include financial savings, patient autonomy, increased appointment availability and reduced pressure on the laboratory. In these unprecedented times, trying to tackle the COVID-19 backlog; we advise all departments to ensure that clear guidance exists.